Live Pregnancy in Non Communicating Horn of Unicornuate Uterus with Placenta Percreta: A Case Report and Review - Minakshi, Rohilla; Parul, Arora; Rashmi, Bagga; Vanita, Jain; G. R. V., Prasad (Journal of Women's Reproductive Health, 2017)
Objective: Mullerian anomalies of the female genital tract are rare and unicornuate uterus is one such variant: it may present with a rudimentary horn with or without a communication. Pregnancy is rare in a non communicating horn and majority of them end up in rupture during first trimester. The ones which progress to fetal viability are around 10 % and may end up in catastrophic hemorrhage with fetal loss at any time. Case report: We hereby report a rare case of unruptured rudimentary horn pregnancy associated with placenta accreta and delivery of a live born fetus at 34 weeks period of gestation. Around ten cases of such an association have been reported in the past. Conclusion: Diagnosis of pregnancy in a non communicating horn of a unicornuate uterus is challenging especially at term. High index of suspicion and timely delivery of a live fetus has major role in achieving best maternal and neonatal outcome.
Keywords: Mullerian; Placenta accreta; Rudimentary horn; Unicornuate.